Urgency of Developing New Regulatory Norms on Subsurface Ownership and Vertical Depth Boundaries in the National Agrarian Law System - Ni Komang Irma Adi Sukmaningsih; Putu Riski Ananda Kusuma; I Putu Andika Pratama (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
This article examines the urgency of developing new regulatory norms governing subsurface ownership and vertical depth boundaries within Indonesia’s national agrarian law system. The study is driven by the absence of explicit legal provisions defining the scope, limitations, and ownership status of underground space, which creates legal uncertainty and potential conflicts in land utilisation, infrastructure development, and urban planning. Utilising a normative juridical method supported by statute, conceptual, and comparative approaches, this research analyses the insufficiency of existing regulations under the Basic Agrarian Law (UUPA), particularly regarding vertical land demarcation and the doctrine of horizontal separation. The findings demonstrate that the current legal framework does not adequately regulate subsurface rights, resulting in normative gaps related to depth limits, administrative procedures, legal protection, and allocation of underground space for public and private interests. The study concludes that Indonesia urgently requires a new normative framework, potentially through the recognition of a distinct Right to Subsurface Space to ensure legal certainty, prevent future ownership disputes, and support sustainable spatial planning.